Women and Children’s Journeys of Exiled to Siberia after January’s Uprising - Cedro, Wojciech (Vade Nobiscum, tom XXI/2019: Studia z historii gospodarczej, kulturowej i społecznej, 2019)
The exile to Siberia was one of the most severe punishment in the Russian Empire’s penal law. Sentenced Poles had to journey thousands kilometres heading East. Besides convicted men, Polish women were exiled as well because of their political activities or personal decision. Indeed, some of Polish women decided to go to Siberia in order to accompany their sentenced husbands or relatives. The history of Polish exiles has not sufficiently been elaborated in historiography. Journey to exile with children is one of the most significant issue in “feminine journeys” topic. Women had to cope with many problems while their journey to Siberia. Among the identified problems were: food’s difficulties, illness, bad living conditions as well as bad attitude of Russian officials. The aim of this article is to describe the conditions of women’s journeys to Siberia. It is focused of their motivation and dedication. Their devotions and often commitments often saved the life of their babies and families.